Pengaruh Kompos Blotong untuk Pertumbuhan Tebu Varietas Bululawang Fase Anakan pada Tanah Areal Pantai Firdaus Kecamatan Asembagus - Gemintang, Tegar Cahya; Asmono, Sepdian Luri; Wahyono, Nanang Dwi; Fatimah, Titien (Agropross : National Conference Proceedings of Agriculture, 2023)
Sugarcane (Saccharum officinarum L.) is one of Indonesia's white sugar producers. Sugar production which continues to soar needs to be balanced with the right cultivation pattern, one of which is by optimizing the growth phase of the sugarcane plant. In the growth phase of the sugarcane plant there is a tiller phase, the tiller phase itself results in the growth of tillers around the mother cane itself. This study examined the soil in the coastal area. In the coastal area there are obstacles to plant growth, such as a lack of nutrients in the soil so that the soil is easily leached which causes the soil to lack nitrogen. The addition of filter cake compost is expected to help maximize the elements in the soil of the coastal area. This study aims to determine the impact of the tillering phase of sugarcane growth from the application of beach area soil with filter cake compost and to determine the appropriate dose of bagasse compost in order to get the best sugarcane crop yields. This study used a non-factorial randomized block design (RBD) with 5 treatments, 4 plant units, and 4 replications. The results of the final project research that has been carried out can be concluded that the effect of filter cake compost on the soil in the coastal area for sugarcane tillering phase showed significantly different results on the parameters of plant height at 14 HST and 42 DAP, while plants aged 70 HST showed highly significant different results. The parameter of the number of tillers showed significantly different results at 42 HST observations. The most influential dose of filter cake compost on the beach area soil was 50% for the Firdaus Beach soil treatment and 50% for the filter cake compost, namely in the third treatment (P2) as evidenced by the results of the highest average plant height parameter compared to other treatments